Rapid discovery of diverse neutralizing SARS-CoV-2 antibodies from large-scale synthetic phage libraries. Issue 1 (1st January 2022) - Yuan, Tom Z.; Garg, Pankaj; Wang, Linya; Willis, Jordan R.; Kwan, Eric; Hernandez, Ana G Lujan; Tuscano, Emily; Sever, Emily N.; Keane, Erica; Soto, Cinque; Mucker, Eric M.; Fouch, Mallorie E.; et al.
ABSTRACT: Coronavirus disease 2019 (COVID-19) is an evolving global public health crisis in need of therapeutic options. Passive immunization of monoclonal antibodies (mAbs) represents a promising therapeutic strategy capable of conferring immediate protection from SARS-CoV-2 infection. Herein, we describe the discovery and characterization of neutralizing SARS-CoV-2 IgG and VHH antibodies from four large-scale phage libraries. Each library was constructed synthetically with shuffled complementarity-determining region loops from natural llama and human antibody repertoires. While most candidates targeted the receptor-binding domain of the S1 subunit of SARS-CoV-2 spike protein, we also identified a neutralizing IgG candidate that binds a unique epitope on the N-terminal domain. A select number of antibodies retained binding to SARS-CoV-2 variants Alpha, Beta, Gamma, Kappa and Delta. Overall, our data show that synthetic phage libraries can rapidly yield SARS-CoV-2 S1 antibodies with therapeutically desirable features, including high affinity, unique binding sites, and potent neutralizing activity in vitro, and a capacity to limit disease in vivo .